Hubungan Antara Tingkat Pendidikan dan Pengetahuan Ibu Nifas dengan Pemberian Asi Eksklusif di Puskesmas Batua Makassar 2019 - Siti Husaidah; Desi Ernita Amru; Sumarni Sumarni (Jurnal Sehat Mandiri, 2020)
The use of exclusive breast milk decreases, due to lack of knowledge and awareness of postpartum mothers, besides the increased promotion of formula milk which causes postpartum mothers to tend to give formula milk. This study aims to determine the relationship between education level and knowledge of puerperal women with exclusive breastfeeding in Batua Puskesmas in 2019. The research design used was cross sectional by taking a sample using Purposive Sampling technique used in 50 respondents at the Pusua Batua Makassar Puskesmas during April to June 2019. Data obtained from questionnaires and processed. The results showed that the Chi Square statistical test between the level of puerperal education with exclusive breastfeeding, obtained p value of 0.304 with (α = 0.05), concluded that there was no relationship between the level of puerperal education with exclusive breastfeeding while Chi Square statistical test between the level of knowledge of puerperal women with exclusive breastfeeding, obtained p value of 0.004 with (α = 0.05), it can be concluded that there is a relationship between the level of knowledge of puerperal women with exclusive breastfeeding. Based on the results of the above research, puerperal mothers should add information and knowledge through various mass media to prepare themselves to face the role of motherhood, so that babies get exclusive breast milk for up to 6 months.